The dinosaurs - Swinton, W. E. (William Elgin) 1900-1994. (London Allen & Unwin, 1970)
Based on the author's book of the same title, London, Murby,1934.
Based on the author's book of the same title, London, Murby, 1934.
Includes bibliographical references (pages 309-321)
Keywords: Dinosaurs; Dinosaurs